Survey of Reconstructive Microsurgery Training in Korea - Moon, Seong June; Hong, Joon Pio; Kang, So Ra; Suh, Hyun Suk (Journal of Reconstructive Microsurgery, 2015)
Background Microsurgical technique in reconstructive surgery is important. Despite recognizing this fact, there are no systematized microsurgery training programs in Korea. The purpose of this study was to diagnose the current training programs and discuss the direction that is needed to improve them.Methods The authors conducted a survey of graduates of a plastic surgery residency program. The questionnaire included the volume of microsurgery, training environment, area of microsurgery, department(s) performing microsurgery, and the frequency with which flaps were used.Results Many specialties other than plastic surgery involved microsurgical procedures. The volume of microsurgery cases was disproportionate between large and small hospitals, creating an imbalance of residents' experience with microsurgical procedures. The increase in microsurgical procedures being performed has increased the number of surgeons who want to train in microsurgery.Conclusion Increasing the number of microsurgery training programs will create more microsurgeons in Korea.
Keywords: training programs; reconstructive surgery; plastic surgery